The black moth ebook - Heyer, Georgette (Historical Romances, 2010)
"Stylish, romantic, sharp, and witty." ?Margaret Drabble A disgraced lord, a notorious highwayman Jack Carstares, the disgraced Earl of Wyndam, left England seven long years ago, sacrificing his honor for that of his brother when he was accused of cheating at cards. Now Jack is back, roaming his beloved South Country in the disguise of a highwayman. And the beauty who would steal his heart Not long after Jack's return, he encounters his old adversary, the libertine Duke of Andover, attempting the abduction of the beautiful Diana Beauleigh. At the point of Jack's sword, the duke is vanquished, but foiled once, the "Black Moth" has no intention of failing again? This is Georgette Heyer's first novel?a favorite of readers and a stirring tale to be enjoyed again and again. "A tale of love and adventure, clearness and charm, and an originality to delight?a tale to stir one's blood." BOSTON EVENING TRANSCRIPT "A romance of the eighteenth century, with a wicked Duke, self-sacrificing elder brother, weak younger brother, highwayman, gambling, abduction, and rescue all complete." THE SATURDAY REVIEW "A well-filled story which keeps the reader pleased." THE TIMES LITERARY SUPPLEMENT "Wonderful characters, elegant, witty writing, perfect period detail, and rapturously romantic. Georgette Heyer achieves what the rest of us only aspire to." KATIE FFORDE